Effect of freeze-thawing process on lipid peroxidation, miRNAs, ion channels, apoptosis and global DNA methylation in ram spermatozoa - Gungor, Ibrahim Halil; Tektemur, Ahmet; Arkali, Gozde; Cinkara, Serap Dayan; Acisu, Tutku Can; Koca, Recep Hakki; Turk, Gaffari (Csiro Publishing, 2021)
This study was carried out to investigate the effect of the semen freezethawing process on the functionality and molecular structure of ram spermatozoa. The temperature of pooled and diluted semen at 38 degrees C (group 1, control) was lowered to 5 degrees C (group 2), and it was subjected to glycerolisationequilibration (group 3), frozen and thawed (group 4). Compared to the control, deterioration in spermatological parameters and significant increases in lipid peroxidation and global DNA methylation levels were observed in groups 3 and 4. When compared with the control, significant downregulation in the levels of miR-485 of group 2, miR-29a of group 3 and let-7a, miR-485 and miR-29a of group 4, and significant upregulation in the levels of miR-107 of group 3 and miR-127 of groups 3 and 4 were detected. In comparison to the control, significant upregulation in the levels of CatSper1, CatSper2, CatSper3, CatSper4, ANO1 and TRPM3 of group 2, CatSper4, ANO1 and TRPM3 of group 3 and KCNJ11 of group 4, and significant downregulation in the CatSper 3 level of group 4 were determined. As a result, the semen freezethawing process causes motility and morphological disorders in rams. This may be due to molecular changes associated with lipid peroxidation in spermatozoa.
Keywords: apoptosis; freeze-thawing; global DNA methylation; ion channels; lipid peroxidation; miRNA; ram semen; sperm characteristics